2006
DOI: 10.1002/macp.200690024
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Macromol. Chem. Phys. 14/2006

Abstract: Cover: This cover illustrates the chemical structure of a highly branched polyurethane obtained using oligomeric poly(ethylene oxide) units in combination with an A2 plus B3 synthetic methodology. Size exclusion chromatography confirms the gradual increase in molar mass without the formation of crosslinked product. The molar mass between branch points permits the formation of more ductile films with facile melt processibility, and maintained ionic conductivity upon salt doping. Further details can be found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…7 Limited availability of AB n monomers increases the use of readily available A 2 þ B 3 monomers for the synthesis of HBP. 8,[9][10][11] After preliminary work by Kim 12 on hyperbranched liquid crystalline polymers, (HBLCPs), synthesized by the AB n approach, the revolutionary work in this field was carried out by Percec et al, [13][14][15][16][17][18] Shibaev et al, 19 and others [20][21][22][23] have reported on photo-addressable dendritic polymers (PADLCPs) containing both mesogenic and photochromic groups. PADLCPs have shown enhanced physicochemical properties and photo and thermally induced physical changes as compared with linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…7 Limited availability of AB n monomers increases the use of readily available A 2 þ B 3 monomers for the synthesis of HBP. 8,[9][10][11] After preliminary work by Kim 12 on hyperbranched liquid crystalline polymers, (HBLCPs), synthesized by the AB n approach, the revolutionary work in this field was carried out by Percec et al, [13][14][15][16][17][18] Shibaev et al, 19 and others [20][21][22][23] have reported on photo-addressable dendritic polymers (PADLCPs) containing both mesogenic and photochromic groups. PADLCPs have shown enhanced physicochemical properties and photo and thermally induced physical changes as compared with linear polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular weight of the chains increased, the DB value decreased because of the low reactivity of the prepolymers. Both the global degree of branching (GDB) and the percentage of the branching part in HPU also decreased [18]. The lap shear strength decreased to 5.61 MPa when nPCDL/nTDI was 0.67.…”
Section: Adhesion Propertymentioning
confidence: 99%
“…Also, the oligomeric A 2 and B 3 methodology offered a facile approach for obtaining products with improved properties and performance. Unal et al [17] and Fornof et al [18] utilized isocyanate end-capped polyether as oligomeric A 2 and triamine or trimethylol as B 3 monomers to get different products. The resulting polymers displayed mechanical properties comparable to their linear analogues [19], but this route needed a lot of solvent to avoid premature gelation.…”
Section: Introductionmentioning
confidence: 99%
“…The exponents a and b express prevalence of viscous over elastic behavior or vice versa; a low exponent expresses linear elastic behavior, whereas an exponent close to 1 corresponds to purely viscous behavior. [23] Applying a non-linear least-squares fit, Equation (7) and (8) were fitted to the experimental data; the fit parameters are given in Table 2. The continuous lines in Figure 3 are the results of the least-squares fit of the generalized Zener model.…”
Section: Rheologymentioning
confidence: 99%
“…Due to the excellent physical properties of TPUs, such as chemical resistance, abrasion resistance, good adhesion and ease of processing, its application can be found in almost all branches of industry branches, including engineering materials, coatings and adhesives, as well as films. [7][8][9][10] Both TPU and PVDF polymers are now being used in airship and balloon manufacturing. Unfortunately, both TPU and PVDF polymers are incompatible at all compositions.…”
Section: Introductionmentioning
confidence: 99%